2020
DOI: 10.3389/fmicb.2020.01917
|View full text |Cite
|
Sign up to set email alerts
|

Human Intestinal Enteroids to Evaluate Human Norovirus GII.4 Inactivation by Aged-Green Tea

Abstract: Human noroviruses are the leading cause of epidemic and sporadic acute gastroenteritis worldwide and the most common cause of foodborne illness in the United States. Several natural compounds, such as aged-green tea extract (aged-GTE), have been suggested as ingestible antiviral agents against human norovirus based on data using murine norovirus and feline calicivirus as surrogates. However, in vitro data showing their effectiveness against infectious human norovirus are lacking. We tested the activity of aged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 45 publications
2
21
0
Order By: Relevance
“…Another potential option for quantifying recovered infectious HuNoV is the fold increase in GE between 1 and 72 hpi in HIEs. Consistent with previous work, we found that fold increases ranged from 10–10,000 and varied from 2–3 logs within tests that used equivalent surface inoculum ( Costantini et al., 2018 ; Chan et al., 2019 ; Randazzo et al., 2020 ). We are not the first to report high variability among measured fold increase in HIEs and this inconsistency remains a key challenge for application of the HIE system to monitoring infectious HuNoV ( Costantini et al., 2018 ; Estes et al., 2019 ; Koromyslova et al., 2019 ).…”
Section: Discussionsupporting
confidence: 91%
“…Another potential option for quantifying recovered infectious HuNoV is the fold increase in GE between 1 and 72 hpi in HIEs. Consistent with previous work, we found that fold increases ranged from 10–10,000 and varied from 2–3 logs within tests that used equivalent surface inoculum ( Costantini et al., 2018 ; Chan et al., 2019 ; Randazzo et al., 2020 ). We are not the first to report high variability among measured fold increase in HIEs and this inconsistency remains a key challenge for application of the HIE system to monitoring infectious HuNoV ( Costantini et al., 2018 ; Estes et al., 2019 ; Koromyslova et al., 2019 ).…”
Section: Discussionsupporting
confidence: 91%
“…HIOs may also provide a platform for evaluating antivirals aimed at chronically infected immunocompromised patients [87]. FDA-approved drugs, natural compounds, and other drugs that block new pathways important for human norovirus or human rotavirus replication are beginning to be reported [81,88,89].…”
Section: Neutralizing Antibodies Therapeutics Vaccines and Viral Inactivation Evaluated In Hiosmentioning
confidence: 99%
“…The antiviral activity of plant metabolites is the subject of many scientific studies [ 23 , 41 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 ,…”
Section: Plant Preparations As Antiviral Agents Against Norovirusesmentioning
confidence: 99%
“…Randazzo et al [ 100 ] observed a complete inhibition of human norovirus GII.4 replication by aged-GTE at concentrations of 1 mg/mL at 37 °C, 1.75 mg/mL for 21 °C, and 2.5 mg/mL at 7 °C.…”
Section: Plant Preparations As Antiviral Agents Against Norovirusesmentioning
confidence: 99%